PsychTech & Health Journal - Universidade de Trás-os-Montes e Alto Douro Escola de Ciências e Tecnologia. Laboratório MASSIVE (Universidade de Trás-os-Montes e Alto Douro, 2017)
Devoted to research and scholarship in areas of psychology and technology.
Keywords: Psychology : Computer simulation; Social Sciences : Periodicals; Humanities : Periodicals; Psychology; Technology; Virtual reality in medicine; Portugal